Recent onset atrial fibrillation: baseline data from Thai subset of RECORD AF study - Sriratanasathavorn, Charn; Pumprueg, Satchana; Boonyapisit, Warangkna (Journal of the Medical Association of Thailand, 2014)
The RECORD AF study is the first worldwide, prospective, observational 1-year longitudinal survey of real-life management of patients with recently diagnosed atrial fibrillation (AF). The authors present here the baseline data of Thai subset of the study. The study enrolled consecutive patients of age > or = 18 years, presenting with and treated for AF (< or = 1 year from diagnosis), visiting office- or hospital-based cardiologists. The main primary objectives were to assess therapeutic success and clinical outcomes in rhythm- and rate-control strategies. Of 209 patients recruited between July and December 2007, 200 were eligible for evaluation (mean age: 62.8 years, SD 12.4; 51% males). Hypertension (49%) and dyslipidemia (36%) were the most common underlying cardiovascular diseases (CVDs). Thirty-six point nine percent of patients were at high risk of stroke (CHADS, score > or = 2). In the previous year 93 (52%) patients were diagnosed with paroxysmal AF and 86 (48%) patients with persistent AF. Rate-control was the main treatment strategy used in 151 (75.50%) of the patients, and was more frequently used in persistent AF (94.20%) than paroxysmal AF (61.3%). The most frequent medication used for rhythm-control strategy was amiodarone (83.7%) and, for rate-control strategy, it was beta-blockers (57%). For antithrombotic medication, antiplatelet agents were used in 92 (46%) patients and oral anticoagulation in 86 (43%) patients. For Thai patients with AF, hypertension and dyslipidemia were the most common underlying CVDs, and rate control was the preferred treatment strategy. The prospective 1-year data will provide insights on current AF treatment strategies.